Study on atomization characteristics for power generation application - Anwar Z.M.; Tan E.S.; Adnan R.; Idris M.A. (Institute of Physics Publishing, 2023)
The world is dependent on two common basic needs which is electricity and water supply. Thus, power generation is the pulse of a country's econmony. However, most of today's power is generated from fossil fuel which is non sustainable. This research aims to study the feasibility of biodiesel to substitute diesel fuel for gas turbine application. The objective is to investigate the atomization characteristics using various blend of biodiesel derived from transesterification of palm oil. There are five types of fuels tested which are pure Diesel, B20, B50, B80 and B100 which were experimentally tested in a spray atomizer to evaluate the relationship of the of the fuel blend ratio with atomization characteristics such as spray cone angle, spray tip penetration and Sauter Mean Diameter. Besides that, fuel chemical properties testing were conducted to ensure the fuel chemical properties for tested fuel meet the standard requirements for gas turbine fuel oil. Result shows that the higher blend of biodiesel will give larger SMD, longer spray tip penetration, and a smaller spray cone angle. The SMD was calculated based on a general equation. Meanwhile, spray angle and spray tip was obtained from photos captured and anlayzed using software. Published under licence by IOP Publishing Ltd.